2003
DOI: 10.1097/00005537-200301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cerebrospinal Fluid Leaks Involving the Temporal Bone: Report on 92 Patients

Abstract: Conservative treatment should be reserved for cerebrospinal fluid otorrhea or otorhinorrhea resulting from head injury. Postoperative and nontraumatic cerebrospinal fluid otorrhea or otorhinorrhea should have early operative intervention. A multilayer technique combining allogenic materials with free autologous grafts is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
158
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 16 publications
1
158
0
14
Order By: Relevance
“…20,21 CT findings are often nonspecific since incidental tegmen defects are a ubiquitous finding in the general population and the radiological appearance of encephalocele and CSF effusion replicate that of chronic otitis media, contributing to the potential for diagnostic delay. Since there is a perceived risk of intracranial infection with encephalocele and CSFF, it is generally agreed that persistent lesions mandate surgical repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 CT findings are often nonspecific since incidental tegmen defects are a ubiquitous finding in the general population and the radiological appearance of encephalocele and CSF effusion replicate that of chronic otitis media, contributing to the potential for diagnostic delay. Since there is a perceived risk of intracranial infection with encephalocele and CSFF, it is generally agreed that persistent lesions mandate surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair is recommended to decrease the risk of impending neurological complications. 3,20,21 Osseous erosion or bony insufficiency may result from trauma, prior surgery, long-standing infection, or destructive processes such as cholesteatoma or tumor. Over the last 2 decades, there has been a substantial increase in the number of reported "spontaneous" cases, where no discernable cause can be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar drains are a safe and well-tolerated adjunct to the various watertight dural closures advocated. 20,21 In this study, there was a statistically significant lower rate of postoperative CSF leakage in patients with a preoperatively placed lumbar drain. The various comorbidities investigated did not contribute to an increased incidence of CSF leak.…”
Section: Discussionmentioning
confidence: 54%
“…These groups of patients are active community groups, and this could be due to a higher prevalence of high-risk behavior in these age groups. These statistics are varying in different societies; results show that the most common brain injury is related to the third decade of life in developed countries (20)(21)(22)(23). Chiu et al revealed that the most common age group 20-29 years in Taiwan (24) and in a study that done in Norway, the most common head injury was reported in the 0-4 and above 75 years age groups.…”
Section: Discussionmentioning
confidence: 99%